Peranan Pedagang Unggas dalam Penyebaran Virus Avian Influenza - Suartha, I Nyoman; Suma Antara, I Made; Saka Wiryana, I Kadek; Sukada, I Made; Wirata, I Wayan; Ritha Krisna Dewi, Ni Made; Kade Mahardika, I Gusti Ngurah (Jurnal Veteriner, 2010)
A questionnaire surveillence have been carried out in three different traditional markets (ie. Beringkitin badung district, Kumbasari in Denpasar, Kediri in Tabanan district) in order to understand the role ofpaultry traders behavior in transmitting of avian influenza virus. Of 150 quationares collected most oftraders (66.7%) kept the animals for 1-3 days before it was marketed. Traders bin Beringkit and Kediri(76.3%) used to mix different species of birds in their cages, whereas none of the traders from Kumbasaridoing that. When hygienec and sanitation aspects were considered (ie. Washing and desinfectan sprayingfor cages) it was found that the behavior of traders varied markedly between the 3 different market. Inconclusion the traders awareness to especially bird flue infection and implementation of biosecurity isvery low.
Keywords: Contribution, Poultry trader, traditional market, avian influenza